2004
DOI: 10.1111/j.1752-0606.2004.tb01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Affection and Conflict in Marital and Parent‐child Relationships

Abstract: In this study, we examined affection and conflict in marital and parent-child relationships, as reported by mothers, fathers, and 9- and 10-year-old children in a community sample of 87 families. Affection and conflict were inversely related within relationships, with mixed findings across relationships. Most reports showed an association between marital and parent-child conflict as well as between marital and parent-child affection. According to fathers, however, the association between marital affection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 47 publications
2
39
1
Order By: Relevance
“…The results of Margolin et al were also confirmed in several other studies (e.g. Fauchier & Margolin, 2004;Forgatch, Patterson, Degarmo, & Beldavs, 2009;Patterson, 1982). These findings implied that the average of all relational conflicts in a family can represent family conflicts, because subscales of the average were consistent with each other and reliable across time (e.g.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…The results of Margolin et al were also confirmed in several other studies (e.g. Fauchier & Margolin, 2004;Forgatch, Patterson, Degarmo, & Beldavs, 2009;Patterson, 1982). These findings implied that the average of all relational conflicts in a family can represent family conflicts, because subscales of the average were consistent with each other and reliable across time (e.g.…”
supporting
confidence: 64%
“…The conflicts in families reportedly affected maladaptation of members of the family (e.g. Fauchier & Margolin, 2004;Forgatch et al, 2009;Patterson, 1982). Daily use of AAs might reflect and predict conflicts in Japanese families.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Carr and VanDeusen 2002;Ehrensaft et al 2003). The link between IPC and child outcomes also has been established by the mediating role of parent-child relationships (Fauchier and Margolin 2004). Several researchers have suggested that problems in the marital subsystem are linked to decreases in the quality of the parent-child relationship and, in turn, negatively affect child behavior (Grych and Fincham 1990).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Secondly, based on the work of Kaufman and Zigler (1987) and other related literature on protective factors (Grych and Fincham 2001), we were interested in the potential protective factor of IPP in moderating the relationship between IPC and young adult conflict management. Lastly, given the established association between parent-child relationships and child outcomes, we wanted to see whether parent-child relations may mediate the intergenerational link to conflict management (Fauchier and Margolin 2004).…”
Section: Introductionmentioning
confidence: 99%